Psychosocial problems of adolescents living in slum riverbank area - Ulfa Azizah; Budi Wahyuni; Fitri Haryanti (Berita Kedokteran Masyarakat (BKM), 2018)
Factors associated with adolescents psychosocial problems in the Code riverbank in YogyakartaPurpose: To identify factors related to adolescent psychosocial problems in the watershed of the Code River in Yogyakarta.Method: The samples are 173 adolescents aged 12-19 years who were selected by consecutive sampling technique based on predetermined inclusion and exclusion criteria. The research instruments used were questionnaire of respondent characteristics, Pediatric Symptom Checklist-Youth Report questionnaire, Child And Adolescent Social Support Scale questionnaire, and residence environment questionnaire. This study used univariate analysis, Chi square test, Fisher test and logistic regression test.Results: A total of 11.6% of adolescents in the Code riverbank area experienced psychosocial problems. Level of education, parental support and the fairness of residence are associated with adolescent psychosocial problems, with level of education as the greatest factor.Conclusion: Adolescent psychosocial problems that occur in the watershed of the Code River in Yogyakarta are related to educational level, parental support and the fairness of adolescent residence.